2020
DOI: 10.3400/avd.ra.20-00002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapeutic Angiogenesis Using Autologous Bone Marrow-derived Mononuclear Cell Implantation in Patients with No-option Critical Limb Ischemia

Abstract: Recently, the limb salvage rate of patients with critical limb ischemia (CLI) has been improved due to the development of revascularization and wound care treatment. However, many patients with CLI are refractory to standard treatments, including revascularization such as endovascular treatment or surgical bypass. Establishment of a new cell therapy is required to improve the limb salvage rate and prognosis in patients with CLI. In 1997, endothelial progenitor cells were found to be derived from the bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…For these patients with no-option CLTI, therapeutic angiogenesis using BM-MNC implantation is a potential recourse. Multiple studies have shown the effectiveness and safety of BM-MNC implantation [13][14][15][16][17][18][19][20][21][22][23]. In 2008, Matoba et al reported that the OS and AFS rates at 3 years after BM-MNC implantation were 80% and 60%, respectively, in 74 patients with no-option CLTI resulting from atherosclerotic LEAD (TACT follow-up study) [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For these patients with no-option CLTI, therapeutic angiogenesis using BM-MNC implantation is a potential recourse. Multiple studies have shown the effectiveness and safety of BM-MNC implantation [13][14][15][16][17][18][19][20][21][22][23]. In 2008, Matoba et al reported that the OS and AFS rates at 3 years after BM-MNC implantation were 80% and 60%, respectively, in 74 patients with no-option CLTI resulting from atherosclerotic LEAD (TACT follow-up study) [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a long-term prognosis analysis performed by Kondo et al, 374 patients with no-option CLTI due to atherosclerotic LEAD had OS rates at 1, 5, and 10 years after BM-MNC implantation of 95.6%, 87.3%, and 68.6%, respectively, and AFS rates of 82.7%, 71.8%, and 59.1%, respectively [20]. In addition, BM-MNC implantation has been reported to improve various indicators of limb ischemia, including the resting pain, pain-free walking distance, ulcer size, and transcutaneous partial pressure of oxygen (tcPO 2 ) [1317, 22, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMMNCs are heterogeneous cell populations including stem cells (SCs), endothelial progenitor cells, monocytes and lymphocytes (39,40). A synergistic effect among the heterogeneous cell populations promotes neovascularisation even in previously avascular tissue (39,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some of the cells included in REX-001 product (enriched for MNC, as well as granulocytes and hematopoietic stem cells expressing CD34) might participate in the paracrine effect. For instance, circulating BM-derived EPC (CD34+CD45+) have been described as powerful angiogenic agents (Yanishi et al, 2020 ). These cells release angiogenic and chemo-attractant factors once migrated into the ischemic tissues, recruiting immune cells (neutrophils, monocytes) and activating other cells that will participate in the inflammatory response and also contribute to vascular remodeling (Beltran-Camacho et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%